FABRICATION OF Mg-Zn-Al HYDROTALCITE AND ITS APPLICATION FOR Pb2+ REMOVAL - Heraldy, Eddy; Rahmawati, Fitria; Ardiyanti, Dwi; Nurmawanti, Ika (Acta Polytechnica, 2019)
The fabrication of Mg-Zn-Al Hydrotalcite (HT) was carried out by the co-precipitation method at various molar ratios. The Mg-Zn-Al HT compound at the optimum molar ratio was then calcined to determine the effect of calcination on the Pb2+ adsorption. The kinetics of the adsorption type was determined by applying pseudo first order and pseudo second order kinetics models. Meanwhile, to investigate the adsorption process, the Freundlich and Langmuir equations were applied to determine the adsorption isotherm. The results showed that the optimum Mg-Zn-Al HT was at a molar ratio of 3 : 1 : 1 with an adsorption efficiency of 73.16 %, while Mg-Zn-Al HT oxide increased the adsorption efficiency to 98.12 %. The optimum condition of Pb2+ removal using Mg-Zn-Al HT oxide was reached at pH 5 and a contact time of 30 minutes. The adsorption kinetics follows the pseudo second order kinetics model with a rate constant of 0.544 g/mg·min. The isotherm adsorption follows the Langmuir isotherm model with a maximum capacity of 3.916 mg/g and adsorption energy of 28.756 kJ/mol.